Reporting companies’ performance – in respect of the international financial reporting standards (IFRS) - Dékán Tamásné Orbán, Ildikó (Applied Studies in Agribusiness and Commerce, 2013)
The role of information became more important due to rapidly changing technical conditions, market and economic regulations in our globalizing world. Several regulations tend to provide the framework for reporting performance and income of the companies, but in different statements performance is inconsistently presented and many kind of evaluation method exist in the practice. These facts led to the demand of properly assess the financial health of an organization, and created a commonly accepted rule-system, which name was International Financial Reporting Standards (IFRS). In this paper I tend to present the statements, definitions and factors, which can have great influence in representing the performance, income of the company in the frame of the IFRS, and reveal the differences between the other accounting regulations (EU directives, Hungarian Accounting Act) in this field.